Systematic Literature Review: Consumer Behavior In The Use Of Credit Cards And Pay Later Payment Systems - Thania Kusmalinda (Jurnal Impresi Indonesia, 2025)
In today's digital era where there are many technological transformations, the ease of conducting financial transactions is one of the things that many people enjoy. One of the services that is widely used is credit cards and pay later systems. A credit card is a payment instrument using a card where the cardholder's payment obligation is fulfilled by the issuer first, then the cardholder is required to make payments at the agreed time, either in full or in installments. Pay later is a type of short-term loan through a digital platform that allows users to purchase goods and then make payments through a series of installments. The purpose of this literature is to investigate using a systematic literature review method (Systematic Literature Review) from various studies to find out how consumer behavior is towards the use of credit cards and pay later. In this study, it was found that demographic factors and consumer behavior have an important role in the use of both payment systems. The use of credit cards is driven by adequate economic factors such as high income. In using the pay later payment system, young consumers (<29 years) tend to have impulsive buying behavior. The drive for a modern lifestyle and a lifestyle that leads to hedonism makes them interested in going into debt. Individuals who have strong self-control tend to be better able to resist excessive use of credit cards and pay later systems. The implication of this finding is to provide input to the public not to use credit cards and pay later excessively because Lots impact negative that will appear.